2017
DOI: 10.1097/wco.0000000000000439
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of migraine and atopy in children and adolescents: myth or a casual relationship?

Abstract: On the basis of clinical features, laboratory findings and some practical clues in children, accurate diagnosis of migraine and atopic disorders are very critical for physicians, pediatricians and algologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…The results of our study are in agreement with those of previous studies in adults and children [6][7][8][9][10][11][12] in that the prevalence of headache was higher in the allergic group than the nonallergic group. Our allergic group consisted of various types of allergy including allergic rhinitis, asthma, atopic dermatitis, and atopic conjunctivitis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of our study are in agreement with those of previous studies in adults and children [6][7][8][9][10][11][12] in that the prevalence of headache was higher in the allergic group than the nonallergic group. Our allergic group consisted of various types of allergy including allergic rhinitis, asthma, atopic dermatitis, and atopic conjunctivitis.…”
Section: Discussionsupporting
confidence: 93%
“…Genetic, environment, and systemic inflammatory response may contribute to headache in chronic allergic disease. 11 A population-based study evaluating the health-related quality of life (HRQoL) in adult headache patients has shown that this comorbid condition is associated with low HRQoL scores. 12 This study aimed to investigate the prevalence of headache in allergic children.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of eosinophils in WBC counts was increased, whereas, in men, the levels of inflammatory markers were consistently lower than those in other classes. The atopic class included enhanced risk for irritable bowel syndrome, cystitis, and migraine [49]. It was associated with mental disorders both in boys/men and in girls/women.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, via neurogenic inflammation and local immune activation, CGRP may participate in psoriasis and possibly rosacea and atopic dermatitis . As there may be pathophysiological links between migraine and atopic dermatitis, there could be dual benefit in CGRP blockade.…”
Section: Potential Benefits Of Blocking Cgrpmentioning
confidence: 99%